2005
DOI: 10.1021/jp050525j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Electronic Structure of Semiconducting Nanotubes Resulting from Different Metal Contacts

Abstract: Examined in this paper is the role of the metal electrode influencing the structure and electronic properties of semiconducting carbon nanotubes near the interface at low bias. Specifically, we present quantum-chemical calculations of finite sections of a (8,0) semiconducting single wall nanotube contacted with gold and palladium clusters. The calculations at the density functional level of theory, which included full geometry optimizations, indicate the formation of bonds between the metal atoms of the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…A similar extent of partial charge transfer, about 0.57-0.60 eV, was observed in both cases, which can be ascribed to the electronic reorganization caused by the interaction of the SWCNT and a high work function metal such as Pd [48,49]. That is, the presence of the 4d electrons of Pd in the antibonding orbitals of the nanotube leads to an enhancement of the electron density in the nanotube, and, consequently, a smaller energy gap [50].…”
Section: Dft Calculation For Pd 4 Adsorption On the Pristine And Funcsupporting
confidence: 55%
“…A similar extent of partial charge transfer, about 0.57-0.60 eV, was observed in both cases, which can be ascribed to the electronic reorganization caused by the interaction of the SWCNT and a high work function metal such as Pd [48,49]. That is, the presence of the 4d electrons of Pd in the antibonding orbitals of the nanotube leads to an enhancement of the electron density in the nanotube, and, consequently, a smaller energy gap [50].…”
Section: Dft Calculation For Pd 4 Adsorption On the Pristine And Funcsupporting
confidence: 55%
“…The improved charge exchange at the Pd-C interface also leads to an enhanced redistribution of the electron density of the contacting layer of the CNT. 16 An additional effect of sd hybridization in Pd is that its Fermi surface is almost entirely composed of d-like states, 26 while that of Au is composed of s-like states, with d DOS lying below E F by about 2 eV. 30 The surface bonding is thus expected to give rise to substantial changes in the electronic contact properties of a CNT due to the extended nature of hybridized states as confirmed evidently in Fig.…”
mentioning
confidence: 94%
“…In an earlier work, it was shown that relaxation of the atomic positions of both the CNT and metal electrodes leads to distinct differences in the electronic structure of the contacting region of the CNT. 16 We have chosen for investigation Pd and Au electrodes since these metals are often utilized for device fabrication and have the same work function, but induce drastically different device performances. The experimental data are elucidated using the calculated transmission curves, density of states ͑DOS͒, and E F location within the gap.…”
mentioning
confidence: 99%
“…To simplify the terminology, the terms "top contact" and "edge contact" will be used here to refer to the side and end contacts, respectively. It has been shown that the edge contact for metal-carbon-nanotube structures substantially reduces the contact resistance compared to side contacts [72]- [75]. Similarly, the first-principle calculations show that the edge-contacted metal-SLG structure exhibits a contact resistance substantially smaller than that of the topcontacted metal-SLG structures [59], [60].…”
mentioning
confidence: 99%